Tulipa sarvestanica (Liliaceae), a new species from south-western Iran - Moein, Fatemeh; Majidi, Ramiar; Khazaei, Zahra; Alipour, Sajad (Phytotaxa, 2023)
In this study, Tulipa sarvestanica (Liliaceae) is described and illustrated as a new species from south-western Iran. Tulipa sarvestanica differs from similar T. systola by having a smaller bulb with arachnoid bristles, smaller fruit (capsule) size, lower black blotch area at the base of the perianth, yellow anther versus purple anther in T.systola. The detailed description, diagnostic features, geographical distribution, habitat, original photographs, phenology, etymology, genome size, conservation status, and related species are presented in this study. Based on the IUCN criteria, the conservation status of Tulipa sarvestanica is classified as endangered (EN) species.